Mechanically driven spin-orbit-active weak links - Jonson, M.; Shekhter, R.I.; Entin-Wohlman, O.; Aharony, A.; Park, H.C.; Radić, D. (Физика низких температур, 2018)
We show that new functionality of spin-orbit-active electronic weak links can be achieved by their timedependent mechanical deformation. As an illustration we use a simple model to calculate the electronic spin current generated by rotating a bent spin-orbit-active nanowire coupled to bulk metallic leads.